CULTIVATOR UNTUK KELOMPOK TANI DESA MUHAJIRIN KECAMATAN JAMBI LUAR KOTA KABUPATEN MUARO JAMBI - Novarini Novarini; Sandi Susanto; Iko Fransisco Siregar; Sandra Lasmana (Politeknik Negeri Sriwijaya, 2021)
This Community Service (PKM) will solve the problems of the Muhajirin Village farmer group which has been constrained by hiring cultivators to plow their agricultural gardens. Muhajirin Village, Jambi Outer District, Muaro Jambi Regency is a plantation area so that plantation products are the only source of community income as a source of daily life. Types of plantation crops grown are chili, eggplant, mustard greens and, long beans. Cultivator rental for farmers is still difficult because the rent is still quite high and also the cost of fuel for the cultivators themselves. Expenditures on rent and cultivator fuel make up a sizeable proportion of the cost of selling crops. This problem is solved by facilitating farmer groups by developing cultivators with lightweight frames so that fuel consumption can also be reduced. . The cost of using fuel for loosening agricultural land and renting a cultivator when starting planting can be saved by Rp. 3,257,370. This reduced value saved reduces farm capital so that the selling price of the harvest can be competitive in the market. The results of training on the use and maintenance of cultivators and continuous assistance have made farmer groups understand and become independent. By understanding and opening up the mindset of farmers, it is hoped that in the future farmers will be more creative in carrying out the farming profession so that the long-term effect of farmers will be prosperous.